Islamic practices among muslims in putrajaya: A preliminary observation - Mohd Noor A.Y.; Mohd Kashim M.I.A.; Ab Rahman Z.; Salleh K.; Mohd Mokhtar A. (Innovare Academics Sciences Pvt. Ltd, 2024)
Tourism is known as the best industry in Malaysia to introduce local uniqueness and cultures as well as attracting more investors to invest in national income. Tourism industry has brought an effort to enhance the quality of services, hospitality, and transportations. It also improves the local income and community lifestyle. However, do these changes affect their religious practices in daily life? This study conducted to investigate community response towards tourism activity and Islamic practices in Muslims community in Putrajaya. This study focuses on Islamic attitude by Muslims and their worships as a religious person in Putrajaya. This study has been conducted by using quantitative methods. The results show that Islam has been practiced and being practiced by most of the Muslims in Putrajaya. There are number of Islamic based NGOs and governments parties holding and conducting activities to enhance the awareness of practicing and teachings of Islam comprehensively. Besides, the response of the Muslims towards tourism activity around Putrajaya, especially in Putra Mosque, has been welcomed greatly and warmly. There are more and more volunteers join the activities and Mosque Tour. However, several local Muslims object some activities organized by volunteers in the Mosque activities especially about allowing non- Muslims visitors entering the mosque. 2020 Innovare Academics Sciences Pvt. Ltd. All rights reserved.